Improved Recharge Estimation from Portable, Low‐Cost Weather Stations. Issue 2 (22nd May 2015) - Holländer, Hartmut M.; Wang, Zijian; Assefa, Kibreab A.; Woodbury, Allan D.
Abstract: Groundwater recharge estimation is a critical quantity for sustainable groundwater management. The feasibility and robustness of recharge estimation was evaluated using physical‐based modeling procedures, and data from a low‐cost weather station with remote sensor techniques in Southern Abbotsford, British Columbia, Canada. Recharge was determined using the Richards‐based vadose zone hydrological model, HYDRUS‐1D. The required meteorological data were recorded with a HOBO TM weather station for a short observation period (about 1 year) and an existing weather station (Abbotsford A) for long‐term study purpose (27 years). Undisturbed soil cores were taken at two locations in the vicinity of the HOBO TM weather station. The derived soil hydraulic parameters were used to characterize the soil in the numerical model. Model performance was evaluated using observed soil moisture and soil temperature data obtained from subsurface remote sensors. A rigorous sensitivity analysis was used to test the robustness of the model. Recharge during the short observation period was estimated at 863 and 816 mm. The mean annual recharge was estimated at 848 and 859 mm/year based on a time series of 27 years. The relative ratio of annual recharge‐precipitation varied from 43% to 69%. From a monthly recharge perspective, the majority (80%) of recharge due to precipitation occurred during the hydrologic winter period. The comparison of the recharge estimates with other studies indicates a good agreement. Furthermore, this method is able to predict transient recharge estimates, and can provide a reasonable tool for estimates on nutrient leaching that is often controlled by strong precipitation events and rapid infiltration of water and nitrate into the soil.